Giant adolescent tubular adenoma of the breast mimicking giant fibroadenoma: a case report - Chang, Shantel; Fairweather, Peta; Sivyer, Paula; Bennett, Ian (International Surgery Journal, 2024)
Tubular adenomas are a rare benign breast neoplasm, often clinically indistinguishable from fibroadenomas or phyllodes tumors. We present a case of the largest adolescent tubular adenoma reported in the literature, measuring 12.5 cm. Radiological evaluation and histopathological assessment of the core biopsy sample was consistent with a giant fibroadenoma. However, the final histopathological analysis of the excisional biopsy sample confirmed a tubular adenoma. This case highlights the clinical conundrum of reaching the definitive diagnosis in a patient with a tubular adenoma. A contemporary review of the clinical features, radiology, histopathology and management options for tubular adenoma of the breast was undertaken.